Nascent to novel methods to evaluate malnutrition and frailty in the surgical patient. (5th December 2022) - Prado, Carla M.; Ford, Katherine L.; Gonzalez, M. Cristina; Murnane, Lisa C.; Gillis, Chelsia; Wischmeyer, Paul E.; Morrison, Chet A.; Lobo, Dileep N.
Abstract: Preoperative nutrition status is an important determinant of surgical outcomes, yet malnutrition assessment is not integrated into all surgical pathways. Given its importance and the high prevalence of malnutrition in patients undergoing surgical procedures, preoperative nutrition screening, assessment, and intervention are needed to improve postoperative outcomes. This narrative review discusses novel methods to assess malnutrition and frailty in the surgical patient. The Global Leadership Initiative for Malnutrition (GLIM) criteria are increasingly used in surgical settings although further spread and implementation are strongly encouraged to help standardize the diagnosis of malnutrition. The use of body composition (ie, reduced muscle mass) as a phenotypic criterion in GLIM may lead to a greater number of patients identified as having malnutrition, which may otherwise be undetected if screened by other diagnostic tools. Skeletal muscle loss is a defining criterion of malnutrition and frailty. Novel direct and indirect approaches to assess muscle mass in clinical settings may facilitate the identification of patients with or at risk for malnutrition. Selected imaging techniques have the additional advantage of identifying myosteatosis (an independent predictor of morbidity and mortality for surgical patients). Feasible pathways for screening and assessing frailty exist and may determine the cost/benefit of surgery, long‐term independence and productivity, and the value of undertaking targeted interventions. Finally, the evaluation of nutrition risk and status is essential to predict and mitigate surgical outcomes. Nascent to novel approaches are the future of objectively identifying patients at perioperative nutrition risk and guiding therapy toward optimal perioperative standards of care.